DETERMINAÇÃO DE Cu²⁺ EM BIOCOMBUSTÍVEIS COM USO DE ELETRODO DE FILME DE BISMUTO, APÓS ELIMINAÇÃO DA INTERFERÊNCIA DO Bi³⁺ - Albuquerque, Daniel dos Santos (2013)
Despite the advantages of bismuth film electrode for the determination of trace metals and organic compounds, the Cu²⁺ is an element that has problems when measured with this electrode, since its potential is very close to the Bi³⁺, causing overlapping of peaks. This work presents an alternative to eliminate the interference of Bismuth in the determination of copper in using bismuth film electrodes (BiFE), prepared ex situ mode. The ethanol fuel samples without pre-treatment and biodiesel samples previously digested were used in order to evaluate this electroanalytical procedure. The optimization of the parameters was performed using a complete factorial design 2³ with center point. After several voltammetric experiments, optimal conditions for the determination of Cu²⁺ were the following: Edep = -1.3 V; tpre = 120s; Frequency: 60 Hertz. The voltammograms using anodic stripping voltammetry method in the square wave mode and their corresponding standard addition curves indicated that the bismuth film electrode provides a sensitive and useful procedure for the determination of Cu²⁺ in biofuels. Experiments carried out by the successive addition of aliquots of a standard solution of Cu²⁺, yielded a linear response of peak current to the concentration of metal ion. Good detection limits have been obtained for the determination of Cu²⁺ in ethanol fuel, soybean oil and tallow biodiesels respectively (4.9 x 10ˉ⁸ mol Lˉ¹; 5.60 x 10ˉ⁸ mol Lˉ¹, 1.79 x 10ˉ⁸ mol Lˉ¹). The accuracy was assessed through recovery test (recoveries of 85.6% to 97.05%) and the precision was expressed by the coefficient of variation that ranged from 10% to 18%. The method was successfully applied to two different samples of biodiesel and ethanol fuel and analyzed in triplicate.